2017
DOI: 10.1038/s41467-017-00462-2
|View full text |Cite
|
Sign up to set email alerts
|

Misalignment with the external light environment drives metabolic and cardiac dysfunction

Abstract: Most organisms use internal biological clocks to match behavioural and physiological processes to specific phases of the day–night cycle. Central to this is the synchronisation of internal processes across multiple organ systems. Environmental desynchrony (e.g. shift work) profoundly impacts human health, increasing cardiovascular disease and diabetes risk, yet the underlying mechanisms remain unclear. Here, we characterise the impact of desynchrony between the internal clock and the external light–dark (LD) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 69 publications
5
113
0
1
Order By: Relevance
“…219,220 Mice that have a misalignment between the internal clock and the external environment (ie housed under a day/night cycle of 20 hours or 30 hours instead of the normal 24 hour cycle) showed altered daily patterns of energy expenditure and carbohydrate and fat oxidation, leading to longer QT intervals. 221 The metabolic alterations were associated with a lower cardiac mitochondrial content. 222 Furthermore, expression of Pgc1a, Mfn1 and Opa1 was downregulated in mice with disturbed circadian rhythms, suggesting that the molecular clock plays a role in the regulation of cardiac mitochondrial dynamics.…”
Section: Interplay Between Circadian Rhythm and Myocardial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…219,220 Mice that have a misalignment between the internal clock and the external environment (ie housed under a day/night cycle of 20 hours or 30 hours instead of the normal 24 hour cycle) showed altered daily patterns of energy expenditure and carbohydrate and fat oxidation, leading to longer QT intervals. 221 The metabolic alterations were associated with a lower cardiac mitochondrial content. 222 Furthermore, expression of Pgc1a, Mfn1 and Opa1 was downregulated in mice with disturbed circadian rhythms, suggesting that the molecular clock plays a role in the regulation of cardiac mitochondrial dynamics.…”
Section: Interplay Between Circadian Rhythm and Myocardial Functionmentioning
confidence: 99%
“…For example ex vivo experiments on rat heart demonstrated that oxidation of exogenous glucose showed significant diurnal variation, whereas no such variations were seen in the oxidation of exogenous oleate . Mice that have a misalignment between the internal clock and the external environment (ie housed under a day/night cycle of 20 hours or 30 hours instead of the normal 24 hour cycle) showed altered daily patterns of energy expenditure and carbohydrate and fat oxidation, leading to longer QT intervals . The metabolic alterations were associated with a lower cardiac mitochondrial content .…”
Section: Lifestyle and Pharmacological Interventions To Target Mitochmentioning
confidence: 99%
“…The resulting 24-hour oscillations in protein expression can be disrupted through environmental disruption (e.g. shift-work schedules), or genetic deletion of core clock components producing inflammatory and metabolic phenotypes (5,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, neglecting our internal 24‐h timing system, which coordinates countless fundamental physiological processes, can exacerbate ill‐health conditions such as psychiatric disorders, obesity, diabetes, cardiovascular disease, and possibly even cancer . Unfortunately, most humans pay little attention to their internal clock and daily light exposure (a key cue for setting and regulating the clock) and too often push their bodies beyond their clocks’ capabilities .…”
mentioning
confidence: 99%
“…Long‐term consequences of circadian disruption may include psychiatric disorders, obesity, diabetes, cardiac disease, and cancers . It is now widely accepted in research that modern lifestyles cause insufficient or inappropriate light exposure on our circadian timing system, which likely contributes to the current epidemic of sleep deficiency in developed societies .…”
mentioning
confidence: 99%